Lack of action–sentence compatibility effect in non-clinical individuals with high autistic traits - Irie, Keisuke; Zhao, Shuo; Aruga, Rieko; Matsumoto, Amiri; Ogawa, Akari; Liang, Nan (Frontiers in Psychology, 2023)
Introduction Patients with autism spectrum disorder (ASD) exhibit atypical responses to language use and comprehension. Recently, various degrees of primary autistic symptoms have been reported in the general population. We focused on autistic traits and examined the differences in mechanisms related to language comprehension using the action–sentence compatibility effect (ACE). ACE is a phenomenon in which response is facilitated when the action matches the behavior described in the statement. Methods In total, 70 non-clinical individuals were divided into low autistic and high autistic groups according to their autism spectrum quotient (AQ) scores. ACEs with adverbs and onomatopoeias were examined using a stimulus set of movement-related sentences. A choice-response task helped determine the correct sentence using antonym adverbs (slow and fast) and onomatopoeia (quick and satto) related to the speed of the movement. Results The low-AQ group showed ACEs that modulated the reaction time in antonym sentences. The high-AQ group showed less temporal modulation, and their overall reaction time was shorter. The low-AQ group showed faster reaction times for onomatopoeic words; however, the high-AQ group showed a tendency to reverse this trend. In individuals with intermediate autistic traits, the angle effect may be moderated by individual differences in motor skills and experience rather than autistic traits. The stimulus presentation involved a passive paradigm. Discussion This study provides insight into language comprehension processes in non-clinical individuals ranging from low to high autistic idiosyncrasy and elucidates language and behavior in individuals at different locations on the autistic trait continuum.